School Principal Digital Leadership in the Development of Mobile-Based IPS Learning Media at UNKLAB Airmadidi Junior High School - Mandey, Larry J; Rawis, Joulanda A.M; Tambingon, Henny N.; Kambey, Joseph (International Journal of Information Technology and Education, 2023)
School principals as leaders in a school have a role important in the development of mobile-based social studies learning media in junior high schools. Unklab Airmadidi Junior High School is one of the Educational Institutions that aim to develop a potency child nation so can compete at the world level. To fulfill these objectives educational institutions, need to develop capable learning media to awaken the interest of students. This study aims for developing android-based IPS learning media on Conditions Geographical Class VIII ASEAN Countries at UNKLAB Airmadidi Junior High School. The research method used in this research is the prototype model. The steps he did, gathering needs designing and prototype evaluation. Mobile-based social studies learning media at UNKLAB Airmadidi Junior High School. This level of feasibility and attractiveness product on good criteria, this proven by responses from students and teachers in good criteria. Based on the results data obtained then mobile-based IPS learning media at UNKLAB Airmadidi Junior High School class VIII can say worthy of implemented in schools.